Quotation/Parenthesis Qur’an Verse Before Beginning Deed In The Structure Of Notary Deed In Sharia Financial Institutions’ Contract - Usman, Sandi Aji; Rasiam, Rasiam (AL-ARBAH: Journal of Islamic Finance and Banking, 2019)
Purpose - This research aims to reveal and describe the issue of Islamic financial institutions' contract structure, the practice of the Qur'an quotation/parenthesis in the notary deed structure in Sharia financial institutions ' contract.Method - The method used in this research is normative juridical, with the processing and analysis of data in a qualitative descriptive way, this research data is sourced from secondary data and supported by interviews from sources as supporting data Secondary. The approach is to study with the regulatory approach of legislation.Result - In Islamic Sharia or fatwa is not regulated about the structure of the deed on the deed authentic or under the hands, but which is governed only the principles or basic rules only. Structure of authentic deed made by notary official, especially the deed in financial institution that includes quotation of Qur'an verses using Indonesian language before deed title does not violate the provisions of UUJN.Implication - The absence of the form of the standard structure of sharia agreement both for sharia transactions and in particular sharia financial institutions should be the financial Services Authority in collaboration with the organization of Indonesian Notary Association (INI) who is already experts to Making authentic deed in the form of raw in accordance with UUNJ.Originality - The focus of this research is to reveal and describe the issue of Islamic financial institutions ' contract structure.Â